Analyzing Constructions of Polytheistic and Monotheistic Religious Traditions: A Critical Multicultural Approach to Textbooks in Quebec. (2nd January 2017) - Abdou, Ehaab D.; Chan, W. Y. Alice
Abstract : How are religious traditions and exchanges between them constructed in textbooks used in Quebec? Through a critical discourse analysis of History and Citizenship Education, and Ethics and Religious Culture textbooks, we find that the Abrahamic monotheistic tradition is valorized, while non-Abrahamic monotheistic traditions and polytheism are either omitted or presented as largely different and exotic, with no potential connections established between the various traditions. As such, we propose a critical multicultural approach and an illustrative model that acknowledges the exchanges and mutual influences among religious traditions. Such an approach should help students from various religious and cultural backgrounds develop an understanding and a respect for diverse human civilizations and religious traditions, thus contributing to fostering inclusive multicultural classrooms.